2023
DOI: 10.1088/1674-4926/44/3/031001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, properties, and applications of Bi2O2Se thin films: A review

Abstract: Two-dimensional materials have shown great application potential in high-performance electronic devices because they are ultrathin, have an ultra-large specific surface area, high carrier mobility, efficient channel current regulation, and extraordinary integration. In addition to graphene, other types of 2D nanomaterials have also been studied and applied in photodetectors, solar cells, energy storage devices, and so on. Bi2O2Se is an emerging 2D semiconductor material with very high electron mobility, modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
(182 reference statements)
0
0
0
Order By: Relevance
“…Various research groups have already demonstrated the potential of Bi 2 O 2 Chbased electronic devices, with Bi 2 O 2 Ch FETs exhibiting high carrier mobility and a large driving current. 86,94,[102][103][104] Simple logic gates have been made from Bi 2 O 2 Ch. Besides, Bi 2 O 2 Ch is also an exceptional choice for infrared photodetectors due to its narrow bandgap and high mobility, [105][106][107][108][109] and its strong spin-orbit coupling effect and ferroelectricity contributing to a large thermoelectric ZT value.…”
Section: Bismuth Oxyhalide Biox (X = CL Br I)mentioning
confidence: 99%
“…Various research groups have already demonstrated the potential of Bi 2 O 2 Chbased electronic devices, with Bi 2 O 2 Ch FETs exhibiting high carrier mobility and a large driving current. 86,94,[102][103][104] Simple logic gates have been made from Bi 2 O 2 Ch. Besides, Bi 2 O 2 Ch is also an exceptional choice for infrared photodetectors due to its narrow bandgap and high mobility, [105][106][107][108][109] and its strong spin-orbit coupling effect and ferroelectricity contributing to a large thermoelectric ZT value.…”
Section: Bismuth Oxyhalide Biox (X = CL Br I)mentioning
confidence: 99%
“…Two-dimensional (2D) materials, due to their unique layer structures and high carrier mobility, have received much attention in the field of electronic and optoelectronic devices [1][2][3][4][5][6][7]. Various high-crystallinity 2D materials have been prepared and used to construct high-performance optoelectronic devices, such as MoS 2 , InSe, MoSe 2 , and so on [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Various high-crystallinity 2D materials have been prepared and used to construct high-performance optoelectronic devices, such as MoS 2 , InSe, MoSe 2 , and so on [6][7][8][9][10][11]. As a new Bi-based 2D semiconductor material with good stability under air conditions, Bi 2 O 2 Se possesses great potential for the construction of infrared photodetectors, phototransistors, and ultrafast lasers [4,5,8,10,12]. Bi 2 O 2 Se has a modest bandgap of 0.8 eV, high carrier mobility (450 cm 2 /(V•s) at room temperature) and concentration (>10 17 cm −3 ), and good thermal and chemical stability [3,4,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations